Pengelolaan Barang Milik Daerah (BMD) Pada Pemanfaatan Aset Daerah Dalam Bentuk Sewa Dan Pinjam Pakai Di Pemerintah Kabupaten Kediri - Sanjaya, Elok; Suwasono, Edy; Mutiara, Nisa (Universitas Islam Kadiri, 2024)
The aim of this research is to analyze the implementation, obstacles and optimization of the implementation of Regional Property Management (BMD) in the utilization of regional assets in the form of rental and lending in the Kediri Regency Government. This research is qualitative research, so data was obtained from interviews with informants. This research uses the analysis technique proposed by Miles & Huberman which includes data reduction, data presentation and drawing conclusions. The results of the research show that: 1) The implementation of Regional Property Management in the utilization of regional assets has been carried out in accordance with the Minister of Home Affairs Regulation Number 19 of 2016 concerning Guidelines for Management of Regional Property and the Regent's Regulation regarding the Utilization of Regional Property in 2022 has been implemented to make implementation easier. . gradual management of regional property; 2) Obstacles in implementing BMD management include publication, location, price and lack of orderly data collection regarding leased assets; 3) Optimization efforts that must be made include having an information system that provides publications to make it easier for the public to access information related to renting and borrowing regional property and making it easier to find out locations that can be rented out.